Cardiovascular imaging of myocardial viability after acute myocardial infarction - Nur Hayati Jasmin
Myocardial infarction is a major cause of death and disability worldwide. In patients with myocardial infarction, the extent and severity of ischemic injury are important prognostic factors for mortality and morbidity. After myocardial infarction, there is a window of opportunity in which intervention can salvage the affected, but still reversible damage caused to the cardiomyocytes. Non-invasive imaging has become a front-line method in the assessment of myocardial viability. A major challenge for present cardiovascular imaging is to identify better ways to assess viable (but threatened) myocardium to stratify patients into optimal treatment pathways. Manganese (Mn2+) is an intraceuutar contrast agent and can enter myocytes through L-type calcium channel, making it an interesting imaging probe for Ca2+ fluxes. Manganese-enhanced magnetic resonance imaging (MEMRI) could provide an assessment on cardiac structure and function as well as in vivo monitoring of intracellular calcium ion (Ca2+) changes. As a central regulator of cardiac contractility, intracellular Ca2+ changes could be used to assess viable myocardium after acute ischemic injury. Thus, the aim of my research was to investigate the accuracy of manganese as a marker of cell viability and develop cardiovascular imaging for assessment of myocardial viability in a mouse model of acute myocardial infarction. To accomplish this, this project is divided into three parts, ultimately leading towards the development of cardiovascular imaging for assessment of myocardial viability after acute myocardial infarction; (1) Characterisation of manganese to optimise dose and ensure safety, (2) Investigation of manganese as an early imaging indicator of cell viability using T1 mapping, and (3) Using manganese-enhanced MRI for functional assessment of the myocardium for early infarct size quantification in acute myocardial infarction: validation against the gold standard, late gadolinium enhancement (LGE-MRI). Keywords: Cardiovascular imaging, Manganese-enhanced MRI (MEMRI), Myocardial viability, Acute myocardial infarction